Pendekatan dan Strategi Pembelajaran Bahasa Arab - Subur, Subur (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Arabic language have specific character and difficulty level which relatively high. In its presentation, this condition requires the appropriate approach, according to student character and its materials. The appropriate approach can derive into strategy that guarantying learning process that more enthusiasm so that can grow the learning motivation and active learning.